2015
DOI: 10.7240/mufbed.73178
|View full text |Cite
|
Sign up to set email alerts
|

Yaprak Senesensi: Fizyolojik ve Moleküler Düzenlenmesine Bakış

Abstract: ÖZETBitkilerde görülen, tüm bitki, organ, doku ya da hücre ölümü ile sonuçlanan önemli bir gelişme süreci olan senesens ile ilgili çalışmalar 1800'lü yılların sonlarına dayanmaktadır. İlk yıllarda gözlemlerden oluşan bu çalışmalar, günümüzde teknolojinin ve genetik biliminin gelişmesiyle yerini kapsamlı biyoteknolojik araştırmalara bırakmıştır. Dünyanın çeşitli yerlerindeki araştırma merkezlerinde bilim adamları senesensin genetik mekanizmasının aydınlatılması ile ilgili deneyler yapmaktadırlar. Üzerinde en ço… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Thus, it indicates that the application of black cumin oil in the form of steam leads to a significant weight loss of samples. It is reported that the most important quality loss in cress leaves after harvest was shrinkage due to water loss, and this loss can be reduced by packaging or coating applications (Ferrante et al, 2004;Sağlam, 2015). However, no literature was found on the effect of black cumin oil vapor on the weight loss of garden cress leaves.…”
Section: Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it indicates that the application of black cumin oil in the form of steam leads to a significant weight loss of samples. It is reported that the most important quality loss in cress leaves after harvest was shrinkage due to water loss, and this loss can be reduced by packaging or coating applications (Ferrante et al, 2004;Sağlam, 2015). However, no literature was found on the effect of black cumin oil vapor on the weight loss of garden cress leaves.…”
Section: Weight Lossmentioning
confidence: 99%
“…Another important quality loss of garden cress leaves is the yellowing resulting from senescence. The postharvest water loss can be delayed by packaging or coating applications, whereas the yellowing caused by chlorophyll degradation cannot be prevented since it is a natural senescence process (Ferrante et al, 2004;Sağlam, 2015). Chlorophyll does not turn into another color pigment during the yellowing process; on the contrary, when chlorophyll breaks down, the yellow pigments already present in the plant become visible (Gross, 1991;Ergün, 2006).…”
Section: Introductionmentioning
confidence: 99%